Production of Organic Polymer Based Monolithic Columns for Anion Separation using High Performance Liquid Chromatography - Dewi Annisa’; Aprilia Nur Tasfiyati; Hermin Sulistyarti; Akhmad Sabarudin (Natural B, Journal of Health and Environmental Sciences, 2015)
Methacrylate-based monolithic columns have been prepared in silanized silicosteel column (100 ´ 0.5 mm id) by in situ polymerization reaction, using glycidyl methacrylate (GMA) as monomer, ethylene dimethacrylate (EDMA) as crosslinker, porogen (1-propanol, 1,4 butandiol, water) and initiator AIBN.  Monolith poly-(GMA-co-EDMA) was then modified with diethylamine and benzyl chloride to obtain ammonium quartener as strong anion exchanger. From the characterization of 4 monolith in this study, monolithic columns poly-(GMA-co-EDMA) with %T 40, %C 25 and polymerization time 24 h has good mechanical stability and permeability, adequate molecular recognition sites (indicated by binding capacity value of 10,119 mg/mL), and has good proportion of flow throughpore and mesopores (45,04% and 41,32% respectively). It can successfully separate the mixture sample of anion consisting of fluoride, bromide, sulfate and nitrate ions by indirect UV detection.